Implementation of red rice consumption education for diabetes mellitus patients: A case study - Bastian, Angga Densi; Budianto, Yudi; Zulkifli, Ahmad Firdaus Bin (Science Center Group, 2024)
Background: Dietary management represents a fundamental component of diabetes care because carbohydrate intake significantly influences postprandial blood glucose levels. In many Asian countries, white rice remains the primary carbohydrate source, which may contribute to higher glycemic responses. Whole grain rice varieties such as red rice contain higher levels of dietary fiber and bioactive compounds that may help regulate blood glucose levels. Therefore, patient education regarding healthier carbohydrate alternatives is essential to support effective diabetes self-management. Objective: This study aimed to examine the implementation of red rice consumption education for diabetes mellitus patients and explore its potential role in supporting blood glucose control in a primary healthcare setting. Methods: This study used a descriptive case study design conducted in the working area of the UPTD Tanjung Baru Community Health Center from February to March 2022. Two patients diagnosed with diabetes mellitus who met predetermined inclusion criteria were recruited as study participants. The intervention consisted of structured education on the nutritional benefits of red rice and guidance on incorporating red rice into daily dietary patterns. Data were collected through observation, structured interviews, documentation review, and literature analysis. The nursing care process included patient assessment, nursing diagnosis formulation, care planning, intervention implementation, and evaluation of patient responses. Results: Baseline assessment indicated that both participants had limited knowledge regarding appropriate dietary management for diabetes mellitus and were uncertain about strategies to control blood glucose levels. Following the educational intervention, participants demonstrated increased awareness of dietary management and greater interest in adopting red rice as an alternative carbohydrate source. Although the nursing problem related to knowledge deficit was not fully resolved during the observation period, participants showed improved understanding of healthy dietary practices and expressed willingness to modify their eating habits. Conclusion: Educational intervention focusing on red rice consumption may improve dietary awareness and support glycemic management among patients with diabetes mellitus. Integrating nutrition education into nursing care programs in primary healthcare settings may contribute to improved diabetes self-management and healthier dietary behaviors.